Viabilidade econômica e ambiental do processo de Fischer-Tropsch para produção de combustível de aviação - Giarrante, Giovanna Goulart (Universidade Federal de São Carlos, 2024)
Tackling climate change and reducing greenhouse gas emissions are a global concern. These gases, in general, come from processes such as energy generation, industrial activities and transport. It is estimated that between 2.5 and 3% of all greenhouse gas emissions come from the aviation sector, which uses kerosene, a fossil fuel derived from petroleum, as fuel. As this is a growing sector, there is concern about developing alternatives that minimize its environmental impacts. Sustainable aviation fuel (SAF) is an alternative to replacing aviation kerosene, as it uses renewable sources such as biomass, natural gas and forestry waste as raw materials. One of the routes of great importance for the production of SAF is through the Fischer-Tropsch process, responsible for producing liquid hydrocarbons from synthesis gas, composed of carbon monoxide and hydrogen. Despite its environmental advantages, the SAF production process is still not used on a large scale mainly due to its high cost, being around 4 times more expensive compared to production from fossil fuels. Because of this, the present work aims to study the economic and environmental viability of implementing the Fischer-Tropsch process for the production of aviation fuel, comparing the different processes and taking into account their costs, environmental impacts and emissions. pollutants, in addition to raising possibilities for reducing these costs in order to enable their production on a larger scale. The results obtained by the analyzes carried out determined that the Fischer-Tropsch process presents environmental advantages in relation to the production of conventional aviation fuels and in some circumstances also in relation to other sustainable production processes, but it still requires improvements that allow a reduction in its cost and make it more competitive.
Economic and environmental feasibility of the Fischer-Tropsch process for aviation fuel production
Keywords: Combustível Sustentável de Aviação; Processo de fischer-tropsch; Sustainable aviation fuel; Fischer-tropsch process; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA